Erasing race: overlooking racial and ethnic disadvantage as a mitigating factor in capital penalty trials - Kleinstuber, Ross (Journal of crime and justice, 2018)
Due to the persistence of structural racism in America, non-whites are more likely to experience hardships related to their race or ethnicity that are relevant to capital mitigation than whites are. Yet, the color-blind ideology of post-Civil Rights America suggests that capital litigators would avoid explicitly addressing racial and ethnic inequality in their mitigation cases, but there has never been a systematic study examining this possibility. This study begins to fill this gap by utilizing an exploratory qualitative content analysis of available capital penalty trial transcripts over an 11-year period in New Castle County, Delaware, to analyze whether capital defense attorneys do, in fact, explicitly discuss racial or ethnic inequality in their mitigation cases or whether they discuss inequality and disadvantage in a purely color-blind fashion. The findings reveal that defense attorneys never explicitly broached the topic of racial inequality, but they did talk about other forms of structural inequality, such as economic deprivation and violent communities. These findings suggest that color-blind ideology does infect capital mitigation, a reality that places non-white defendants at a further disadvantage in capital penalty proceedings.